The Challenge of Home Allergen Re-introductions Using the Ladder Approach in Children With Non-IgE Mediated Gastrointestinal Food Allergy - Meyer, Rosan; De Koker, Claire; Dziubak, Robert; Godwin, Heather; Reeve, Kate; Chebar-Lozinsky, Adriana; Foong, Ru-Xin; Skrapac, Ana-Kristina; Ellmer, Marlene; Shah, Neil (Frontiers in Allergy, 2021)
Background: Oral food challenges remain the most reliable method for allergy confirmation. Although consensus guidelines have been published to unify Immunoglobulin E (IgE)-mediated challenges, this does not exist for non-IgE mediated gastrointestinal allergies outside of Food Protein Induced Enterocolitis Syndrome. We therefore set out to establish the use of home introduction protocols (HIP) for confirmation of food allergy for milk, soya, egg and wheat using a ladder approach in children with non-IgE mediated allergy. Materials and Methods: Patients with suspected non-IgE mediated gastrointestinal allergies (0–16 years) were recruited following symptom improvement on an elimination diet. All children had skin prick or specific IgE tests to rule out IgE-mediated allergies prior to suggestion the HIP. Number of trials and outcome was documented. HIPs were developed using a published ladder approach for cow's milk as baseline and final dose was calculated based on guidelines for food protein induced enterocolitis syndrome and portions for age from the National Diet and Nutrition Survey. First foods were baked/highly processed and every 4th day patients moved to a more unprocessed/unheated food. Results: From 131 recruited patients, 117 (89.3%) followed the HIP for food allergens. No adverse events were documented. In more than 50% of cases one attempt at the HIP was sufficient to establish allergy status, but many required 2–5 attempts before the outcome was clear. About half of the children were fully tolerant to foods they initially eliminated: 36, 26 and 30% were partially tolerant to milk, soya, and egg and only 15% achieved partial tolerance to wheat. Wheat was the allergen introduced earliest, followed by soya, cow's milk and egg. Conclusions: This study indicates that home HIPs are safe in non-IgE mediated gastrointestinal food allergy and that the ladder approach may be useful in re-introducing allergens in children at home with non-IgE mediated gastrointestinal allergies. From this study we can also conclude that tolerance to processed/baked allergens was observed in many children. Further studies should be performed on the HIP and ideally reintroduction should occur pre-defined time intervals.